Strategi Pengembagan Usaha Fashion Thrift Melalui Pendekatan Analisis SWOT di Kota Maumere, Kabupaten Sikka (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the development strategy of the Jeanete business, located in Maumere City, Jl.  Kesehatan No.  3, Lorong Masuk SDK Yos Sudarso, using the Strengths, Weaknesses, Opportunities, and Threats (SWOT) approach.  The research employs a descriptive qualitative method with data collected through observation, interviews, and documentation of the Jeanete business operations.  The results indicate that the main strengths of the business include affordable product prices, unique item variations, and increasing consumer interest in preloved products.  However, Jeanete also faces several weaknesses, such as dependence on supplies from outside the region, limited stock availability, and fluctuating bale prices.  On the other hand, opportunities include the growing trend of thrifting among young consumers and rising demand for environmentally friendly products.  The threats faced by the business involve increasing competition, shifting consumer preferences, and the risk of products not passing quality control.  Based on these findings, the development strategy for Jeanete should focus on improving product quality, strengthening digital promotion, and maintaining more stable supply management.